An analysis of translation errors made by brazilian students of english - Maria da Conceição Magalhães Vaz de Mello (1982)
The purpose of this thésis is to do an analysis of the errors contained in translations from Portuguese into English written by Brazilian students. This topic has been chosen for two main reasons: first, there are few studies of errors made by Brazilian students in the process of learning English; second, many language teachers still consider interference from the mother tongue the only source of errors in foreign language learning. Errors due to interference from the foreign language itself have often been disregarded.